Immature Caenorhabditis elegans motor neurons control early embryo behavior via both synaptic and nonsynaptic GABA release - James Marvel-Coen; Evan Ardiel; Jian Zhao; Stephen Nurrish; Joshua M. Kaplan (Proceedings of the National Academy of Sciences, 2026)
Prenatal brain activity has long lasting effects on subsequent neurodevelopment. It is unclear if early brain activity is dominated by cell intrinsic, synaptic, or nonsynaptic mechanisms. We address this question by analyzing Caenorhabditis elegans embryo behavior in snf-11 mutants, which lack a plasma membrane GABA reuptake pump (orthologous to GAT1). At 510 to 570 min postfertilization, embryo motion was transiently and potently inhibited in snf-11 GAT1 mutants, which precedes formation of most nerve ring synapses. This transient motion inhibition requires GABA synthesis in DD motor neurons and UNC-49 GABA A receptors in body muscles. When motion inhibition occurs, DD neurons have not yet completed neurite outgrowth. Genetic analysis suggests that motion inhibition was mediated by both synaptic and tonic GABA release from DD motor neurons. These results suggest that DD neurons control embryo behavior prior to completing their developmental maturation.